Liberia Forestry Development Authority : An Institutional Capacity Assessment - World Bank Group (World Bank, Washington, DC, 2020)
This report presents the findings from an institutional capacity assessment of Liberia's Forestry Development Authority (FDA) based on a survey of FDA employees. The FDA plays a pivotal role in managing Liberia's forest resources, and its Strategic Plan (2018–2030) prioritizes institutional strengthening for achieving its vision of “sustainable forestry for sustainable development.” The FDA employee survey was conducted to provide scientific evidence on the main organizational and personnel dimensions of institutional capacity, including staff skills, management practices, staff attitudes and behaviors, experiences of corruption and undue political interference, stakeholder interaction, and factors determining project success. A total of 438 FDA employees, or approximately 82 percent of the staff, were interviewed, and the sample covered Monrovia andthe field offices. The survey’s findings are relevant to key FDA strategic pillars of improving staff productivity, strengthening internal governance, and improving the agency’s customer service charter. These findings identify four key reform pillars that, when supported by a strong foundation of better data and more regular monitoring and evaluation, will help strengthen FDA’s institutional capacity: improving skills through merit-based recruitment and competency-based training; stronger management practices, in particular, performance assessments, targeting and monitoring; more equitable pay; and greater community engagement. Administrative data and regular staff surveys can be the basis of a key set of indicators on public employment and management that the FDA can use to assess progress toward institutional strengthening.